Spin determination via α-d angular correlations and α-transfer DWBA analysis in 18F high-energy states - Etchegoyen, M. C.; Sinclair, D.; Etchegoyen, A.; Belmont Moreno, E. (North Holland Publishin Co., 1983)
Fil: Etchegoyen, M. C. Comisión Nacional de Energía Atómica; Argentina